Examination of a Theoretical Model of Streaming Potential Coupling Coefficient - D. T. Luong; R. Sprik (International Journal of Geophysics)
Seismoelectric effects and streaming potentials play an important role in geophysical applications. The key parameter for those phenomena is the streaming potential coupling coefficient, which is, for example, dependent on the zeta potential of the interface of the porous rocks. Comparison of an existing theoretical model to experimental data sets from available published data for streaming potentials has been performed. However, the existing experimental data sets are based on samples with dissimilar fluid conductivity, pH of pore fluid, temperature, and sample compositions. All those dissimilarities may cause the observed deviations. To critically assess the models, we have carried out streaming potential measurement as a function of electrolyte concentration and temperature for a set of well-defined consolidated samples. The results show that the existing theoretical model is not in good agreement with the experimental observations when varying the electrolyte concentration, especially at low electrolyte concentration. However, if we use a modified model in which the zeta potential is considered to be constant over the electrolyte concentration, the model fits the experimental data well in a whole range of concentration. Also, for temperature dependence, the comparison shows that the theoretical model is not fully adequate to describe the experimental data but does describe correctly the increasing trend of the coupling coefficient as function of temperature.